Práticas leitoras literárias nos 'Caminhos e Estações': o perfil leitor experienciado dos estudantes de nono ano das escolas públicas municipais de Passo Fundo - Cunert, Fátima Cristina dos Passos (2025)
This thesis aims to examine the reading profile of ninth-grade students from public municipal schools located in the city of Passo Fundo/RS, who participated in the 8th National Literature Day, linked to the University of Passo Fundo and with the endorsement of the City Hall of Passo Fundo, in 2017. During the event, the young people engaged in literary reading activities, called 'Paths and Stations'. The research includes the following institutions: E.M.E.F. Antonino Xavier, E.M.E.F. Daniel Dipp, E.M.E.F. Dyógenes Martins Pinto and E.M.E.F. São Luiz Gonzaga. The aim is to investigate how students' literary preferences are shaped by interaction with education professionals. Given the contemporary transformations related to communication, the advent of new technologies and the different ways of reading, it is essential to understand how adolescents interact with literature in order to enhance learning opportunities; they also participated in the "Jornada em Movimento" in 2017, and the information was obtained through questionnaires and interviews. For each class, two students were chosen - one with a reading habit and the other with little familiarity with this practice - who, in turn, were nominated by the Portuguese Language teacher. The research seeks to understand how literary reading practices were established and how these students, as readers, engaged in this process. Furthermore, it aims to explore how the workshops and activities carried out are interconnected with the formation of the reader profile experienced and what the effect is of the experiences in the Reading Stations and in the construction of the appreciation for literature. The methodology adopted in this research is classified as exploratory and descriptive, incorporating both qualitative and quantitative aspects. The theoretical foundation is based on authors such as Larrosa (2003, 2020), Petit (2017), Santaella (2015), Zilberman (2016) and Failla (2024). This study is also characterized as field research, involving 188 students from the main schools, in addition to being classified as action research, since it investigates social and educational processes in which the participants play an active role. Data collection was carried out through questionnaires and semi-structured interviews, allowing a detailed analysis of the reading profile of the subjects with literature. The results lead to the conclusion that the literary reading initiatives implemented by Pré-Jornadinha and Jornadinha had a positive impact on the formation of more competent readers. It was noted that reading, when done in a dialogical and reflective manner, can function as a powerful means of transformation, both on a personal and social level. However, the research also highlighted some challenges. The lack of continuity in literary activities that follow the Jornadinha, and the lack of environments designed for free reading in educational institutions, restrict the development of a lasting reading habit. Therefore, it is essential to highlight the need to revitalize the "Jornadinha" as a tool to promote a culture of reading among students in the public education system of Passo Fundo.